Design and Analysis of Memristor Emulators Using Operational Transconductance Amplifier - Gupta, Suchitra (My University, 2019)
There are three basic elements which are generally required to form any electrical circuit. Each element is defined by one of the relations among current i, voltage v, charge q and flux Φ. The relation between voltage and current defines a resistor, the relation between charge and voltage defines a capacitor, the relation between flux and current defines an inductor. Among these, one relation between charge and flux is missing. This missing element was predicted by Leon Chua in 1971. After Chua’s prediction not many people started working towards memristor due to lack of understanding and available resources. After three decades, people have started working over this topic and thus there is a huge scope of research available in this direction. In May 2008, researchers at HP Labs published a paper announcing a model for the physical realization of the memristor. This paper has drawn significant attention of researchers and made this topic alive. A new era in electronics has come due to the advantages offered by memristors in various applications.Now, memristor is expected to be used in numerous applications of analog signal processing, digital signal processing and in memory industry. But, memristor is still not easily available in device form due to complexity in fabrication, higher cost that restricts its use in real time applications. Therefore, the researchers and engineers got motivated to design the memristor emulator circuits which mimic the properties of memristor. Various emulator circuits are being reported by using various active building blocks such as current conveyers (CC) , voltage differential current conveyor (VDCC) , operational transconductance amplifier (OTA), current conveyer transconductance amplifier (CCTA) and differential voltage current conveyor transconductance amplifier (DVCCTA). Among these blocks, OTA is becoming popular due to its availability as off-the-shelf component, simpler in design, electronic tunable and also requires less number of passive components to realize memristor. In the thesis, different configurations of OTA have been designed to realize memristor emulator circuits. These configurations are designed to provide the advantages for memristor emulator circuits such as improvement over range of transconductance, high transconductance gain and linearity. The different structures of OTA have been used in both floating as well as grounded memristor emulator circuits. These grounded and floating memristor emulator circuits are compared with existing configurations. A new grounded and floating memristor emulator has been proposed by using CDTA, OTA and a grounded capacitor. Both incremental and decremental configuration can be formed with a slight change in the circuit. The simulations results are verified by using Mentor Graphics ELDO tool using TSMC 0.18µm process parameters.
M. Tech. (VLSI Design)
Keywords: CDBA; Memristor; Memristor emulator; OTA